Evaluating the Ability to Consent to Research: A Twenty‐Year Track Record. Issue 2 (26th February 2022) - Matera‐Vatnick, Mikaela; Todman, Katherine W.; Wakim, Paul G.; Sullivan, Haley K.; Squires, Carol; Brintnall‐Karabelas, Julie; Doernberg, Samuel N.; Danis, Marion
ABSTRACT: Occasionally, the ability of prospective research participants to consent may be uncertain. Yet standardized capacity‐assessment tools may not suffice to determine the ability to consent to a particular research protocol. This study consisted of a retrospective review of the outcomes of an alternative approach used by the Ability to Consent Assessment Team at the National Institutes of Health. Of 944 individuals evaluated over 20 years (1999‐2019), 70.1% were determined to have capacity to consent to participate in research. Of those who lacked capacity to consent and were subsequently evaluated for their ability to assign a surrogate, 86.0% had the ability to do so. The findings demonstrate that establishing a task‐specific approach for assessing the capacity of potential participants to consent to a variety of research protocols can facilitate safe and ethically justifiable inclusion of individuals whose ability to consent is initially uncertain.